The effect of international visitors on poverty alleviation in Mexico: An approach from the misery index - Fernando Sánchez López (Journal of Applied Economics, 2022)
The effectiveness of tourism as an instrument in combating poverty has emerged as an important subject of research. Tourism's impact on poverty has traditionally been analyzed from the perspective of income or household consumption per capita. In contrast to these approaches, we analyzed the effect of the arrival of international visitors on poverty in Mexico by way of its impact on a modified misery index. To carry out this study, we used a bivariate structural vector autoregressive model, which indicates a negative unidirectional relationship from the international visitors to the misery index. Additionally, the historical decomposition shows that during the first COVID-19 wave, the changes in the international visitors highly explained the variations in the misery index.
Keywords: 330; International tourism; Okun's misery index; poverty; structural VAR